2009
DOI: 10.1089/lap.2008.0127.supp
|View full text |Cite
|
Sign up to set email alerts
|

Microlaparoscopic-Assisted Gastrostomy in Children: Early Experiences with Our Technique

Abstract: In our opinion, MAG is a feasible, safe procedure in children. Technically, it is a simple method, particularly in cases where percutaneous tube placement is not feasible. It combines the advantages of microlaparoscopy and open surgery. It is easy to perform in children and allows a primary gastrostomy tube placement. Parents and nursing staff also seem satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…[12][13][14] Additionally, in the present feasibility study of microlaparoscopic colon dissection for HD, it was demonstrated that the microlaparoscopic approach could be successfully performed in cases of previous laparotomy, colostoma placement, and laparoscopy and in subjects after severe postpartal enterocolitis episodes. Microlaparoscopy is an attempt to further minimize the access trauma of laparoscopic procedures, and we suggest that downsizing the instruments and scopes used in pediatric surgery is beneficial for infants and children.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…[12][13][14] Additionally, in the present feasibility study of microlaparoscopic colon dissection for HD, it was demonstrated that the microlaparoscopic approach could be successfully performed in cases of previous laparotomy, colostoma placement, and laparoscopy and in subjects after severe postpartal enterocolitis episodes. Microlaparoscopy is an attempt to further minimize the access trauma of laparoscopic procedures, and we suggest that downsizing the instruments and scopes used in pediatric surgery is beneficial for infants and children.…”
mentioning
confidence: 65%
“…Since 2005, the microlaparoscopic approach was introduced at our department for various procedures, and it was successfully used instead of conventional laparoscopy in children. [12][13][14] After having gained experience in microlaparoscopy, in a prospective feasibility study, we began to perform the colon mobilization and dissection for HD using 2-mm instruments and miniscopes exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in small children low pressure CO 2 insufflation should be sufficiently provided no desaturation occurs. [55]…”
Section: Points To Consider For Thoracoscopymentioning
confidence: 99%
“…Além disso, pode ser utilizada precocemente, geralmente após 6-24 horas, 2 embora seja considerada segura a administração praticamente imediata 17 ; a ocorrência de extravasamento também é significativamente menor que nas gastrostomias cirúrgicas 'clássicas'. 18 Contudo, estas vantagens esbatem-se face à colocação cirúrgica por laparoscopia, nomeadamente por ser viável realizar a gastrostomia, com colocação imediata de botão, sem cicatriz adicional (Fig. 3); acresce que esta técnica, por disponibilizar visualização direta de todo o procedimento, permite eleger com maior acuidade o local da gastrostomia e apresenta uma incidência significativamente menor de complicações graves.…”
Section: Gastrostomiasunclassified